Kauwaeranga in Context - Sinclair, Fergus (Victoria University of Wellington Law Review, 1999)
Much controversy throughout the world has surrounded aboriginal territorial and nonterritorial rights. In New Zealand, the decision last century of Chief Judge Fenton in Kauweranga has been upheld as a major precedent for nonterritorial Maori fishing rights. The author explores in much greater detail than before the circumstances of the decision, and claims that without such an examination old authorities such as Kauwaeranga will be of limited value.